A Review on Reconfigurable Antennas for Wireless Communication Systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reconfigurable antennas have the great utility in smart and adaptive. Thereconfigurable characteristic offer many advantages in wireless applications such as fourthgeneration (4G) and fifth generation (5G) mobile terminals. A reconfigurable antenna needs tohave an adequate number of active elements for the reconfiguration of antenna characteristics.These high-quality active elements increase the cost and biasing complexity of the networks tocontrol the circuitry. The current distribution in the radiating patch is responsible of antenna’scharacteristics, which can be change through changing the current flow in the patch. To changethe current distribution in radiating patch the active element (switches) are required such asMEMS switch, varactor diode and p-i-n diodes. Therefore, we have presented a review on thereconfigurable antennas for advance wireless terminals, which are recently proposed by the otherauthors.